Analisis Sistem Informasi Mengukur Kepuasan Pelayanan Pelanggan Dengan Metode Servqual - Satria Satria (Sekolah Tinggi Teknik - PLN, 2019)
PT Matahari Department Store Tbk is one company that stands in the fashion world. At this time in measuring customer satisfaction is still managed manually by using a piece of paper called VOC (Voice Of Customer). The data can be stored in the VOC map (Voice Of Customer) record can be stored in a different place. This results in not taking a while when making a subscription to follow up in improving service to customers. System design in measuring customer service to improve work efficiency and can be useful in helping work creativity and progress in services that are increased by the company takes precedence. The method that can be used to measure customer satisfaction is one of them is the servqual method. This method makes a comprehensive customer satisfaction assessment for services in the department store field. Assessment is carried out on the quality of 5 dimensions of service quality, namely: Tangibles or direct evidence, Reliability or reliability, Responsiveness or responsiveness, Assurance or guarantee, Emphaty or attention. Customer dissatisfaction arises because of the gap between customer expectations and the reality of service performance felt.